THE ROLE OF SOCIAL MEDIA IN INCREASING PUBLIC HEALTH AWARENESS - Ramadhani, Syaira Zhieka; Nasution, Sabrina Cahyati; Adriani, Novita Dwi; Daulay, Rangga Muriansyah; Purba, Sri Hajijah (LPPM Univ. Ibn Khaldun Bogor, 2024)
This study highlights the role of social media in enhancing health awareness among the community. Based on a systematic literature review, this research analyzes the current situation where social media serves as a primary platform for disseminating health information. However, issues such as the spread of inaccurate information and hoaxes can mislead the public. The proposed solutions include digital literacy education for the community to better filter information, as well as collaboration with health professionals and relevant institutions to provide valid health content. The conclusion of this study is that social media has great potential in improving health awareness, but it requires proper control and education to maximize its benefits and minimize the risk of spreading misinformation.